A qualitative analysis of formerly incarcerated women’s perspectives on a prison-based perinatal support program - Mollee K. Steely Smith; Julia E. Hooper; Maegan Calvert; Melissa J. Zielinski (BMC Pregnancy and Childbirth)
Abstract Background People who are pregnant while incarcerated are a high-risk population with complex and often unmet health care needs. Although perinatal support programs are becoming more common in carceral settings, limited research has examined individuals’ interest in and experiences with these programs. This study explored formerly incarcerated perinatal individuals’ knowledge about, participation in, and perceptions of currently existing and potential future components of a perinatal support program in a Mid-southern women’s state prison. Methods Semi-structured interviews were conducted with individuals who were incarcerated during pregnancy (N = 15; 100% identified as women; 66.7% white), the majority of whom gave birth while in custody (n = 13; 86.7%). Participants were asked about three existing elements of the program (support group, lactation, childbirth education), and a hypothetical fourth element, doula support. Data was analyzed using a qualitative description approach via MAXQDA. Results Most women viewed the program positively and expressed satisfaction with the program. Nearly all women participated in at least one program component; fourteen (93.3%) participated in the support group and two (13.3%) participated in lactation. Most of the thirteen women who did not participate in lactation reported this was due to ineligibility per institutional policies (69.2%), but some indicated non-participation was due to personal choice (23.1%) or not knowing that lactation was offered (7.7%). Seven of the nine women who were ineligible for lactation (77.8%) expressed desire to participate if eligible. While the childbirth education component was ultimately found to be unavailable during incarceration for most women who were interviewed due consequences of the COVID-19 pandemic, the great majority of women (86.7%) indicated they would have participated had it been offered. Nearly all women (93.3%) also reported interest in a hypothetical doula support component to the program should it become available. Conclusions Incarcerated perinatal individuals are both interested in and voluntarily participate in prison-based perinatal support programs and view these services as acceptable and beneficial to their needs. Findings highlight the importance of expanding access and addressing institutional barriers to improve perinatal care within these settings.